Oil palm Analisis Capaian ISPO (Indonesian Sustainable Palm Oil) Perkebunan Kelapa Sawit Pola Swadaya di Kabupaten Rokan Hulu: ACHIEVEMENT ANALYSIS OF ISPO (Indonesian Sustainable Palm Oil) PALM OIL PLANTATIONS BY INDEPENDENT PATTERN IN ROKAN HULU DISTRICT - Mifta Intan Sari Sari (Jurnal Agribisnis, 2022)
Oil palm is one of the leading plantation commodities in Indonesia. The advantages of palm oil make Indonesia the most significant producer and exporter of palm oil in the world. The high global and international market demand for environmentally-friendly palm oil is one of the reasons for the Indonesian government to implement the ISPO (Indonesian Sustainable Palm Oil) policy in 2011. The ISPO is the standard set by the Indonesian government for sustainable oil palm plantations. The ISPO certification must be made by all oil palm plantation merchants. This study aims to determine the achievements of implementing ISPO certification on independent oil palm smallholders in Rokan Hulu by looking at some of the principles in ISPO certification, namely plantation legality, plantation organization and management, environmental management and monitoring, and sustainable business improvement. This research was conducted in one of the districts in Riau Province, namely Rokan Hulu. The results of this study show that independent oil palm smallholders in Rokan Hulu are still unable to implement the best standards for oil palm plantations following the principles and criteria contained in ISPO certification. Keywords : ISPO, Oil palm, Replanting